Addressing Gender Bias and Bullying in Islamic Boarding Schools: Challenges and Solutions - Hafidzi, Anwar; Nurdin, Nurdin; Lutfi, Lutfi (Muadalah, 2024)
This study examines the problem of gender bias and bullying in boarding schools in Indonesia with the aim of identifying the problem profile, influencing factors, and applicable solutions. The research method used is a qualitative approach with an in-depth literature review with a literature approach and several journals that discuss bullying in boarding schools.The research findings show that gender bias is manifested in restrictions on access to education and stereotyped gender role expectations among santri. The separation between male and female students has become a pesantren tradition with the aim of more focused access to education. However, stereotypical views of gender roles also affect various activities in pesantren. Bullying appears in the form of verbal intimidation, social exclusion, and physical violence between students, and even victims of bullying can experience significant psychological distress. The implications of this study are the need for increased awareness and education on gender equality and anti-bullying, the adoption of structured anti-discrimination and anti-bullying policies, and strengthening the role of supervisors and counselors in pesantren. This study provides a foundation for further efforts in developing inclusive education policies and effective intervention strategies to address issues of gender bias and bullying in pesantren education settings.